Rancang Bangun Dongkrak Elektrik Berbasis Pengendali Proportional Integral Derivative (PID - andi asni b; mayda waruni (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2018)
Abstract— Proportional Integrator Derivative (PID) controller, which aims to set a variable value with stable and precision in an instrument system using a feedback (closed loop) on the system. RPM readings rotation of DC motor that drives the screw jack to be used as a reference control. After implementing the motor rotation speed control system with PID controller jack using the 3-point setting of 60, 50 and 40 RPM. The measurement results show the average speed of each point setting. When the set point average of 60 RPM rotation speed of the motor jack to 56 RPM with an average of 4 RPM below the set point. When the set point average of 50 RPM rotation speed of the motor jack to 47 RPM with an average of 3 RPM below the set point. And when the set point average of 40 RPM rotation speed of jack motor to 37 RPM with an average of 3 RPM below the set point